Robot-assisted brachytherapy of the bladder with long distance support using video conferencing - Mascarenhas, Francisco; Maes, Kris; Marques, Fernando; Formoso, Rui; Antunes, Telma (Journal of Contemporary Brachytherapy, 2017)
Purpose: The frontline treatment for localized muscle-invasive bladder carcinoma (MIBC) is radical cystectomy. However, a significant percentage of this population is elderly with either severe co-morbidities or suboptimal general health, increasing the per- and post-operative risk when undergoing a radical cystectomy. Conservative treatment options have been implemented such as robot-assisted laparoscopic brachytherapy (RALB), a minimally invasive therapeutic approach ensuring excellent results in terms of local control, survival, and low morbidity. The treatment was supported successfully long distance using videoconferencing by an expert group from the Netherlands. Material and methods: An 81-year-old man was treated with RALB. The patient was submitted to external beam radiotherapy (EBRT) in a total dose of 40 Gy in 20 fractions. A partial cystectomy followed by implantation of three catheters along the scar and brachytherapy was completed. A total dose of 25 Gy in 10 fractions was administered with dose points calculated at 5 mm from the catheters. Results: Dose planning was characterized by an homogeneity index of 62.3% and overdose index of 19.7%. Other conformity indexes were analyzed. Patient was discharged at the fourth day after the procedure. The clinical response after 6 months was documented. Conclusions: The previously reported good rates of tumor control and survival, and the excellent tolerance and low morbidity support RALB as a promising approach for selected groups of patients with localized MIBC. This case illustrates the ability to expand efficiently this technique, particularly among inexperienced medical teams.